2016
DOI: 10.1590/0004-282x20160008
|View full text |Cite
|
Sign up to set email alerts
|

Speech disorders did not correlate with age at onset of Parkinson’s disease

Abstract: Parkinson' s disease (PD) is a neurodegenerative disorder characterized by loss of dopamine-producing cells and affects mainly individuals over 60 years but a young onset subtype is also well recognized 1 . Motor limitations observed in PD are often attributed to basal ganglia dysfunction associated with decreased dopaminergic input to the sensorimotor region of the striatum 2 .The progressive neuronal loss is associated with a variety of motor and non-motor deficits in PD patients. In addition to the predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
2
7
0
6
Order By: Relevance
“…It has been estimated that as high as 89% of PD populations eventually experience speech impairment [ 22 ]. In line with our findings, Dias et al also found that speech impairment does not correlate with the age of onset, but it is more likely to happen in people with more severe PD [ 23 ]. Moreover, according to our findings, speech problems were also more common among males, and those with a more symmetric PD.…”
Section: Discussionsupporting
confidence: 92%
“…It has been estimated that as high as 89% of PD populations eventually experience speech impairment [ 22 ]. In line with our findings, Dias et al also found that speech impairment does not correlate with the age of onset, but it is more likely to happen in people with more severe PD [ 23 ]. Moreover, according to our findings, speech problems were also more common among males, and those with a more symmetric PD.…”
Section: Discussionsupporting
confidence: 92%
“… 9 - 10 There appears to be a correlation between the degree of dysarthria and other factors such as motor status, disease progression and cognitive functions. 11 - 12 It is estimated that less than 5% of PD patients have engaged in speech rehabilitation, 13 the most common reasons for non-adherence being physical limitations, lack of companion, long travel distances and financial costs. 14 …”
Section: Introductionmentioning
confidence: 99%
“…frontal inferior, la corteza premotora, el área motora suplementaria, ínsula, la región orofacial de la corteza motora primaria, los ganglios basales, el tálamo y el cerebelo 15,25,26 . La disartria hipocinética en la EP se atribuye a la afectación subcortical que interrumpe las redes motoras de ganglios basales-tálamo-corteza para la programación y ejecución del habla.…”
Section: Metodologia De Busqueda De Informacionunclassified
“…La disartria hipocinética en la EP se atribuye a la afectación subcortical que interrumpe las redes motoras de ganglios basales-tálamo-corteza para la programación y ejecución del habla. Algunos estudios muestran activaciones anormales en las áreas motora orofacial primaria, motora suplementaria, premotora, prefrontal, ganglios basales y cerebelo durante la producción del habla parkinsoniana 15,25,26 .…”
Section: Metodologia De Busqueda De Informacionunclassified